Impacts of Psychosocial stress on Physiology and Psychology substantially based on effort reward imbalance model: A comprehensive review - Jahan, M. An. Nayem (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.